The Resilience of Tortor Sirittak Hotang Simalungun Through The Development of Dance Learning Media - Sitti Rahmah; Yusnizar; Raden (Institut Seni Indonesia Denpasar, 2024)
Resilience in this research is intended to maintain Tortor Sirittak Hotang Simalungun by developing dance learning media, which is utilized primarily in the Unimed FBS Dance Education Study Program. This research aims to add reference material for teaching as well as an effort to maintain the traditional art of Simalungun dance, which is feared to be drifting away with the times, where today's young generation does not know or is not interested in learning traditional dance art. Tortor Sirittak Hotang is a typical Simalungun dance depicting the Simalungun people's work activities as rattan farmers. This activity inspired the people of Simalungun to create a dance (Tortor) that tells how people live in search of rattan (spiritual hosting). Tortor Sirittak Hotang began to appear around the 1990s at the Rondang Bintang Party. Tortor Sirittak Hotang is not yet widely known to the younger generation of Simalungun, nor has it attracted their interest in learning more about it. This digital technology-based Simalungun dance learning media product results from research and development (R&D). Data collection through needs analysis, literacy studies, and documentation. Data analysis was obtained by distributing questionnaires to validate research products. This research indicates that the Simalungun dance media product, validated by material and media validators, is very suitable for use as a dance learning media for FBS Unimed Dance Education Study Program students.